Educational life-forms Deleuzian teaching and learning practice - Cole, David R.; SpringerLink (Online service). (Rotterdam SensePublishers, 2011)
This book takes the philosophy of Gilles Deleuze and applies it to educational practice. To understand how and why to do this, David R Cole puts forward the notion of educational life-forms in this writing, which are moving concepts based on Deleuzian principles. This book turns on and through the construction of the philosophy of life in education. The life-forms that will come about due to the philosophy of life in education rest on epiphanies, the virtual and affect. The author looks to infuse educational practice with the philosophy of life, though not through simple affirmation or a construction of counter metaphysics to representation in education. This book uses Deleuze for practical purposes and sets out to help teachers and students to think otherwise about the current praxis of education."--Publisher's website
Electronic reproduction.
Keywords: Deleuze, Gilles -- 1925-1995.; Education -- Philosophy; Electronic books